The practice of scaling landscape-based fertilizer advisory in Ethiopia: Drivers, pathways, and strategies for upstream-downstream integration for scaling - Gizaw Desta; Mequanint B. Melesse; Murat Sartas; Getachew Agegnehu; Abiro Tigabie; Gizachew Legesse; Henok Desalegn; Tilahun Amede; Mangi Lal Jat; Rebbie Harawa (Sustainable Futures)
Smallholder farming in Ethiopia faces challenges with poor nutrient use efficiency and low yields. Addressing these issues requires site-specific nutrient management strategies. Since 2020, a landscape-based fertilizer advisory has been developed, co-validated, and piloted to improve fertilizer use efficiency, lower costs for smallholder farmers, and promote environmental sustainability. This effort has been catalyzed by the CGIAR Excellence in Agronomy Initiative and driven by demand partners from the local to the national level. This paper systematically analyzes the process and practice of scaling up this innovation, using an agricultural innovation system (AIS) analysis. Using a contextualized innovation scaling framework, we examine the dissemination process and mechanisms, key drivers of scalability, the institutional collaboration and governance of the scaling process and practices. We emphasize the importance of a demand-driven, participatory, and collaborative scaling process that guides the analysis of scaling drivers, diffusion pathways, barriers, and strategies for responsible scaling from both local (horizontal scaling) and national (vertical scaling) perspectives. This scaling process has led to a localized, farmer-relevant nutrient management approach that delivers optimized and cost-effective advisory services. Consequently, farmers have demonstrated significant improvements in understanding (86–94 %) and implementing the landscape-based advisory (75–91 %), with usability scores ranging from 4.2 to 5.2 out of 7. This paper provides insights and guidance to facilitate the transition from delivery to scaling agricultural innovations on a large scale, emphasizing the importance of a contextualized science of scaling and pathways, customized strategies, successful partnerships, responsible scaling, and ongoing efforts to overcome emerging barriers to effective scaling.